Margaritaria nobilis L.F. (Phyllanthaceae): Ethnopharmacology and Application of Computational Tools in the Annotation of Bioactive Molecules - Johan Carlos C. Santiago; Carlos Alberto B. Albuquerque; Abraão de Jesus B. Muribeca; Paulo Roberto C. Sá; Sônia das Graças Santa R. Pamplona; Consuelo Yumiko Y. e Silva; Paula Cardoso Ribera; Enéas de Andrade Fontes-Júnior; Milton Nascimento da Silva (Metabolites, 2022)
Margaritaria nobilis is a shrubby species widely distributed in Brazil from the Amazon to the Atlantic Rainforest. Its bark and fruit are used in the Peruvian Amazon for disinfecting abscesses and as a tonic in pregnancy, respectively, and its leaves are used to treat cancer symptoms. From analyses via UHPLC-MS/MS, we sought to determine the chemical profile of the ethanolic extract of M. nobilis leaves by means of putative analyses supported by computational tools and spectral libraries. Thus, it was possible to annotate 44 compounds, of which 12 are phenolic acid derivatives, 16 are O-glycosylated flavonoids and 16 hydrolysable tannins. Among the flavonoids, although they are known, except for kaempferol, which has already been isolated from this species, the other flavonoids (10, 14, 15, 21, 24–26, 28–30, 33–35, 40 and 41) are being reported for the first time in the genus. Among the hydrolysable tannins, six ellagitannins present the HHDP group (6, 19, 22, 31, 38 and 43), one presents the DHHDP group (5), and four contain oxidatively modified congeners (12, 20, 37 and 39). Through the annotation of these compounds, we hope to contribute to the improved chemosystematics knowledge of the genus. Furthermore, supported by a metric review of the literature, we observed that many of the compounds reported here are congeners of authentically bioactive compounds. Thus, we believe that this work may help in understanding future pharmacological activities.